Signal processing systems theory and design - Kalouptsidis, N (Wiley series in telecommunications and signal processing., 1997)
A highly practical, detailed, and comprehensive resource containing all the tools and methods required to design signal processing systems This meticulously prepared reference will bring you up to speed on signal processing systems, a multidisciplinary technology with widespread applications in telecommunications, robotics, controls, pattern recognition, and image processing. Thorough, clear, and highly practical, this book emphasizes tool development as well as signal processing design and shows readers how to perform a variety of tasks. These include signal compression and coding, modulation, encryption, filtering for signal enhancement and noise removal, pattern classification, error control coding, prediction to estimate future behavior, feedback control, and identification to locate a plant or signal source operating in an uncertain environment. No other book offers this wide range of tools and techniques essential to the design of signal processing systems. Extensively illustrated and supplemented with extensive appendixes, it provides Complete coverage of all major signal and systems representations Detailed descriptions of the phases involved in the design of a signal processing system Applications, algorithms, and simulations designed to be run using MATLAB Examples of various types of signals and systems, including analog, discrete, digital, multidimensional, and stochastic. A balanced account of both theoretical and implementation issues